2008
DOI: 10.1007/s12114-008-9031-1
|View full text |Cite
|
Sign up to set email alerts
|

Taking Advantage of an Untapped Pool: Assessing the Success of African American Head Coaches in the National Football League

Abstract: Hiring discrimination, Coaching, Pro football,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…For the longer period of 1989 through 2007, Branham (2008) confirms Madden’s results as he also finds that African American coaches outperform whites in the regular season and perform at similar levels in the playoffs. He does not consider, however, whether performance differences by race change after the initiation of the Rooney Rule affirmative efforts.…”
Section: Head Coach Records By Race 1990–2002 and 2003–2009supporting
confidence: 68%
See 1 more Smart Citation
“…For the longer period of 1989 through 2007, Branham (2008) confirms Madden’s results as he also finds that African American coaches outperform whites in the regular season and perform at similar levels in the playoffs. He does not consider, however, whether performance differences by race change after the initiation of the Rooney Rule affirmative efforts.…”
Section: Head Coach Records By Race 1990–2002 and 2003–2009supporting
confidence: 68%
“… 11 Branham (2008) used playoff seeding in his analyses of racial differences in playoff success. Of course, seeding in the playoffs, regular season win record and pre-season ranking are highly correlated.…”
mentioning
confidence: 99%
“…For example, Holmes (2011) finds evidence of salary discrimination against African American MLB players, while Berri and Simmons (2009) find evidence of salary discrimination against African American quarterbacks in the NFL. Branham (2008) and Madden (2004) bring to light that African American coaches in the NFL are seemingly on a shorter leash and held to a higher standard than similar white coaches. Also, Kanazawa and Funk (2001) find evidence of customer discrimination against African American NBA players.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research involving Black coaches in the National Football League (NFL) has found changes over time in their performances relative to White coaches (Branham, 2008). With that in mind, the fifth and sixth rows split the sample between games in 2005-2010 and games in 2010-2015.…”
Section: Resultsmentioning
confidence: 99%